Multiperiod heating storage control for distributed electric heating considering wind curtailment accommodation. (22nd October 2019) - Yang, Yulong; Yan, Gangui; Mu, Gang
Summary: Electric heating is perceived as an effective way to tackle heavy wind curtailment and severe smog in northern China, wherein distributed electric heating (DEH) accounts for a significant proportion. However, more research is required with regard to its thermal characteristic. This paper presents the multiperiod heating storage control for a DEH load to reduce wind curtailment. To cope with intermittent wind power, a novel multi‐objective and layered optimization method is proposed by decomposing the integrated electricity and heating optimization problem into the electricity optimization subproblem and the heating optimization subproblem. Additionally, the influence of solar radiation on the thermal characteristic of the DEH load is considered in the building thermal process model when creating the day‐ahead schedule of the DEH load control, and this is also regarded as the basis for grouping DEH users. Last, the simulation and economic feasibility analysis based on the data measured by the DEH system of Jilin Province, China, are carried out. The results show that this proposal can reduce the electricity cost for DEH users by 25%, and the critical feasible price for curtailed wind power is varying between 86.1 and 115.3 yuan/MWh according to different subsidy methods. Abstract : Multiperiod heating storage control of distributed electric heating load is proposed. The distributed electric heating is used for curtailed wind power consumption. The solar radiation is introducedin distributed electric heating load modeling.